2019
DOI: 10.1167/iovs.18-26214
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Model of Acute Allergic Conjunctivitis Induced by Continuous Exposure to Particulate Matter 2.5

Abstract: PURPOSE. Several pieces of epidemiologic evidence have indicated PM2.5 (particulate matter with a diameter of 2.5 lm or less) as a causing factor of allergic conjunctivitis, but without experimental elucidation of mechanism. In the present study, PM2.5 in solution was directly applied to the mouse ocular surface to elucidate whether PM2.5 might cause allergic conjunctivitis, and its underlying mechanisms were analyzed. METHODS. ICR mice were challenged for 18 consecutive days with eye drops containing PM2.5 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 46 publications
(70 reference statements)
1
17
0
Order By: Relevance
“…is discrepancy could be attributed to indoor and outdoor air pollution and the increased pollen due to climate change and global warming [11][12][13][14]. Several reports have shown that AC is closely related to asthma, rhinitis, and other allergic diseases, which seriously affects the quality of life of patients and productivity [5][6][7][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…is discrepancy could be attributed to indoor and outdoor air pollution and the increased pollen due to climate change and global warming [11][12][13][14]. Several reports have shown that AC is closely related to asthma, rhinitis, and other allergic diseases, which seriously affects the quality of life of patients and productivity [5][6][7][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…When treated with AECM, the immune cells and eosinophils in the conjunctival tissue of mice were reduced by 28.23% ± 5.1% and 60% ± 4.5%, respectively, compared to EAC mice ( Figure 2D ). When conjunctival goblet cells (one typical type of mucus-secreting cells) ( 38 40 ) were examined, similar patterns of the SRW-induced increase in EAC group and the inhibitory effects of AECM were observed ( Figures 2E, F ).…”
Section: Resultsmentioning
confidence: 60%
“…Among the six sources that contributed to the PM 2.5 in the city, “soil” had a significant positive association with ocular symptoms. Tang et al [ 15 ] described a murine model of acute allergic conjunctivitis induced by continuous exposure to particulate matter (PM 2.5 ). The mice that were challenged with eye drops containing PM 2.5 in increasing concentrations displayed more eyelid edema, tearing, and scratching behavior, and also had a higher goblet cell density in the upper palpebral conjunctiva, showing extensive eosinophil infiltration in the meibomian glands and ocular surface as well.…”
Section: Discussionmentioning
confidence: 99%